A study to evaluate the pattern of microorganisms causing early post-operative wound infection in patients undergoing orthopaedic surgery with implant for closed fracture or disease in medical college and hospital, Kolkata - Mukherjee, Subhankar; Mukherjee, Jayanta; Kumar, Sanjay; Misra, Subarna; Bhatta, Ranajit; Sengupta, Manideepa (International Journal of Research in Orthopaedics, 2020)
Background: For all orthopaedic surgical procedures with implant, infection at the operative site has always been recognized as a potential complication. The present study was done to evaluate the pattern of causative microorganisms in post-operative infection after orthopaedic surgery with implant in Medical College and Hospital, Kolkata. Methods: This study was Institution based cross-sectional observational case study. Patients population were selected from the patients, who were admitted or came for follow up in the Department of Orthopaedics, who had undergone surgery with implant for close fracture and disease and developed early (<3 months) post-operative wound infection The samples were collected and were sent to the Department of Microbiology, Medical College & Hospital, Kolkata for isolation and identification of the microorganisms and their antimicrobial susceptibility were done. Results: Maximum infections were detected and wound swabs were sent for culture in 2nd week of surgery followed by 3rd week. Only 10% (8 cases) had infection beyond 8 weeks. Plates with screws were used in 37 cases (46%) and nails in 15 cases (19%). It was been seen that infection in case of hip prosthesis were significant that is 8% (6 cases) which included four cases of hemiarthroplasty and two cases of total hip arthroplasty. Conclusions: The data suggests that there is preponderance of Gram- negative infections in operated orthopaedic patients, but Staphylococcus aureus predominates the infectious agents as the sole pathogen. Klebsiella species and pseudomonas species are second and third most common pathogens respectively.